ANTIFUNGAL ACTIVITY OF CHITOSAN AND ITS QUATERNIZED DERIVATIVE IN GEL FORM AND AS EDIBLE COATING ON CUT CHERRY TOMATOES - Assis, Assis BG (Journal of Agricultural Sciences (Belgrade), 2018)
The antifungal activities of medium molecular weight chitosan and its derivative hydrosoluble salt N,N,N-trimethylchitosan, were examined as both gel and as a solid protective coating against three common food spoilage fungi (Penicillium sp, wild Aspergillus sp and one standard strain of Aspergillus flavus). The chitosan derivative is characterized by having permanent positive charges and is expected to have a higher antimicrobial activity than commercial chitosan. In gel form the minimum inhibitory concentration (MIC) resulted in the same value for both polymers against all tested fungi (> 2.0 gL-1). Against the Penicillium the derivative presented a significant fungistatic action within the concentration range of 0.2 to 0.6 gL-1. When applied as protective coatings on freshly cut cherry tomatoes, the chitosan appeared to be more effective in forming films and preventing fungal infestation than the derivative. Less than 20-25% of samples were infected after one week of incubation when compared to control (uncoated) and derivative treated samples.
Keywords: minimally processed tomatoes; protective coatings; Penicillium; Aspergillus; antifungal activity; chitosan; antifungal